Implementasi E-Commerce Untuk Mendukung Perekonomian Masyarakat Lokal Di Desa Selatbaru - Nadra Sagita; Suha Saputri; Rizki Maulana; Titin Sumarni (Penerbit Hellow Pustaka, 2024)
The increasingly rapid development of technology and information currently requires people to become familiar with and always be in touch with the internet. The internet, which was previously considered a pseudo technological sophistication, has now transformed into a real world that has succeeded in creating a new lifestyle for modern humans, starting from cellphones, netbooks, laptops and various other gadgets. The existence of MSMEs in Selatbaru Village, which is located in Bantan District, Bengkalis Regency, is very developed when compared to other villages in Bengkalis Regency. However, these MSMEs have not yet used e-commerce. The type of research used in this research is using a qualitative descriptive type, namely research in the form of words, images and not numbers in collecting data with the aim of describing events obtained based on data in the field. The factor that most influences MSMEs in Selatbaru Village in utilizing e-commerce is that it can facilitate product promotion and marketing. Without continuous promotion and marketing of products, their business will be eroded in increasingly tight business competition. Apart from that, MSME players also realize that they have to keep up with increasingly modern developments and the increasing demand to be more creative in running their business.